Configuração do mesossistema entre professores e pais de alunos com deficiência - SOUZA, Priscilla Bellard Mendes (Universidade Federal do Pará, 2014)
The relation between the parents and the teachers has been seen as a basic foundation for the good school performance, and development of the pupils. This study presents the data of a research about the analysis of the relations established between the parents and the teachers of children with disabilities that are registered in a public school in Belém of Pará. For such, four parents and five teachers had been interviewed preliminarily; later different focal groups for parents and teachers had been accomplished. The data had been analyzed qualitatively, searching to investigate the relation in function of three specific variables: the content, the quality and the frequency. Such variable can be understood in relation to the activities that the parents make together with the school, how they do such activities and in which frequency they do. The analysis of the data showed that the familiar participation in the school reality is still found sufficiently distant of what could be considered the ideal, mainly, when it is related to the school inclusion of children with disabilities, although it is contained in the pedagogical project of the school that the paper of the school is to stimulate the participation of the community. The data had also disclosed that the parents rarely go to the school, limiting themselves only to take and to pick up the pupils and rarely they talk with the teachers about other subjects, they only talk about some problems that the pupil has presented in the classroom. Although the results show a widely negative reality, the teachers and the parents believe that it must have been a continuous participation of the family in the school, however both do not develop activities to proportionate such approach. In only one of the cases, a teacher showed to develop activities that bring the family more closely to the children daily school. Specifically in relation to the parents of students with disabilities, the situation reveals sufficiently similar to the parents of “normal” children, however beyond the natural distance, still has barriers of preconception and discrimination with the children with disabilities, what consequently reflects in the relation with these families.